PERAN POLA ASUH ORANG TUA DALAM PENANGANAN ANAK HIPERAKTIF (ADHD) DI SLB PAEDAGOGIA SURABAYA - Muhammad Haidarsyah Kasyfillah; Muhammad Rizki Imansyah; Khorriyatul Khotimah (JURNAL JUDIKHU, 2023)
Humans must grow and develop as long as they live. ADHD is an increase in activity to a certain level so that the behavior disorder that occurs has a negative impact, this makes the inability to sit still in class or eat, talk continuously, be disorganized, stubborn, behave erratically. This study aims to find out how the role of parenting parents in handling hyperactive children (ADHD). In this research method used qualitative research where data collection is done through the interview method. In this study, data collection techniques used primary data in the form of observations and interviews with teachers and parents. The results of the study show that the parenting style that must be applied to hyperactive children is that they need special personal assistance and the existence of democratic and authoritarian parenting in educating hyperactive children so that they are able to control their emotions and also so that children become psychologically calm and comfortable and not easily angry, and requires intermediaries between teachers and parents in dealing with children with ADHD so that they are aligned and able to develop according to their development both at school and in their surroundings.